It takes two to tango: a reply to our MMT critics - Françoise Drumetz; Christian Pfister (European Journal of Economics and Economic Policies: Intervention (EJEEP), 2023)
We reply to the critics who contributed the other papers in the same issue of this journal. In the first part of the article, we indicate those remarks addressed to us, which we deem inappropriate to answer. The second part deals with the remarks we find useful to answer, which relate to money, monetary policy and central banking on the one hand, and to fiscal policy on the other hand. The third part recalls remarks we made in our previous publications and that our critics did not wish to consider, whereas this might have helped them in amending their theory. In the fourth part, we conclude that an opportunity to engage in a more fruitful debate may thus have been missed: indeed, it takes two to tango.
Keywords: B52; E12; E42; E62; E63; H30; H62; H63; 330; Fiscal policy; functional finance; Modern Monetary Theory; monetary policy